2004
DOI: 10.1016/j.cbpb.2003.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Betaine improves growth, but does not induce whole body or hepatic palmitate oxidation in swine (Sus scrofa domestica)

Abstract: Dietary betaine may reduce carcass fat in growing pigs. We explored the effects of betaine on short-term growth and in vivo and in vitro fatty acid oxidation. Pigs were housed in metabolism crates and fed diets containing either 0% (control), 0.125% or 0.5% betaine at 80% of ad libitum energy intake. Fatty acid oxidation was measured during intravenous infusions of 1-C-palmitate and in hepatocytes incubated in the presence or absence of betaine and carnitine. 13CO and palmitate isotopic enrichments were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
(36 reference statements)
1
17
1
2
Order By: Relevance
“…In this study, betaine had no effect in serum NEFA and similar results have previously been reported (Matthews et al, 1998;Øverland et al, 1999). Furthermore, it is interesting to point out that whole body or hepatic fatty acid oxidation was not affected by betaine in growing pigs (Wray-Cahen et al, 2004), suggesting that reduction in adipose accretion must be via a mechanism other than oxidation. Nevertheless, Huang et al (2006) reported increased NEFA but no change in TG of finishing pigs fed diets supplemented with betaine.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, betaine had no effect in serum NEFA and similar results have previously been reported (Matthews et al, 1998;Øverland et al, 1999). Furthermore, it is interesting to point out that whole body or hepatic fatty acid oxidation was not affected by betaine in growing pigs (Wray-Cahen et al, 2004), suggesting that reduction in adipose accretion must be via a mechanism other than oxidation. Nevertheless, Huang et al (2006) reported increased NEFA but no change in TG of finishing pigs fed diets supplemented with betaine.…”
Section: Discussionsupporting
confidence: 89%
“…However, Wray‐Cahen et al . () showed that betaine had no effect on whole body or hepatic palmitate oxidation in swine. The difference might be attributed to the different animal models, ages and experimental periods between the experiments.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that betaine administration increases hepatic concentrations of methionine and Sadenosylmethionine, while reducing homocysteine and cystathionine in rats and mice [1,2]. Thus, betaine may be integrally involved in the lipid metabolism via its role in phosphatidylcholine synthesis and fatty acid oxidation because carnitine is required for the transport of long-chain fatty acids into mitochondria [3]. Previous studies have shown that betaine administration protected the liver from hepatotoxicants, such as ethanol and lipopolysaccharide (LPS) [4,5].…”
Section: Introductionmentioning
confidence: 97%